A Test of Purchasing Power Parity: Asia Pacific and Latin America - Catherine S. F. Ho; M. Ariff (Asian Academy of Management Journal of Accounting and Finance, 2009)
Finding evidence of the theoretical relationship between exchange rate and inflation has been a difficult proposition in an exchange rate market, despite many studies in developed markets. Three recent papers employing a new research design, Theil’s Divisia index method, found that this relationship holds only in the long run, given the sticky price hypothesis. However, this relationship has not yet been tested for economic regions with close trading networks. The use of this method enables us to resolve a longstanding issue as to the veracity of Purchasing Power Parity (PPP). This paper presents results that suggest long-run equilibria in two close trading regions, within both developed and emerging economies. We believe that these findings on long-run equilibrium and the length of time to equilibrium will enrich the literature on exchange rate market behaviour in both developed and emerging markets.